Luminescent pro-nitroxide lanthanide complexes for the detection of reactive oxygen species. Issue 3 (11th December 2019) - Barré, Richard; Mouchel dit Leguerrier, Damien; Fedele, Lionel; Imbert, Daniel; Molloy, Jennifer K.; Thomas, Fabrice
Abstract : A DOTA-based ligand appended with a pro-nitroxide moiety has been chelated to trivalent Eu and Yb, giving luminescent complexes. Under Fenton conditions both are converted into iminonitroxide and subsequently nitronyl nitroxide complexes. Abstract : The DOTA-based ligand H3 L (5 ) appended with a pro-nitroxide moiety has been synthesized. The europium and ytterbium complexes 5Ln show metal-centred luminescence. They react with ROS in aqueous media to give a transient iminonitroxide and a stable nitronylnitroxide radical authenticated by EPR, with change in luminescence.